SISTEM PAKAR KEBUTUHAN GIZI UNTUK IBU MENYUSUI BERDASARKAN DIAGNOSA KONDISI IBU BERBASIS WEB DENGAN METODE ANALYTIC HIERARCHY PROCESS (AHP) - Purwaning Tyas Sukmawati; Safni Marwa; Hanantatur Adeswastoto (Jurnal Inovasi Teknik Informatika, 2025)
Kampar Regency is one of the regencies or cities with the lowest coverage of exclusive breastfeeding. Factors that influence the low level of exclusive breastfeeding include the mother’s physical condition, the mother’s limited knowledge and the baby’s physical limitations. The limited number of experts causes some breastfeeding mothers to have difficulty in determining the nutrition consumed to increase breast milk. To overcome this, a computerized system is needed with the knowledge and expertise of an expert, namely an expert system. Expert systems are able to provide specific knowledge and information, and can be used to provide advice and decisions on problems that occur. This expert system is website-based, explained using the Analytical Hierarchy Process (AHP) method and built using the PHP programming language, Laravel framework and MySQL database with a waterfall model development method that produces structured and clear stages. The results of this expert system are recommendations for nutritional needs for breastfeeding mothers based on the mother’s diagnosis.